2021
DOI: 10.1177/03611981211031221
|View full text |Cite
|
Sign up to set email alerts
|

Demand Responsive Transit Simulation of Wayne County, Michigan

Abstract: Demand responsive transit (DRT) can provide an alternative to private cars and complement existing public transport services. However, the successful implementation of DRT services remains a challenge as both researchers and policy makers can struggle to determine what sorts of places or cities are suitable for it. Research into car-dependent cities with poor transit accessibility is sparse. This study addresses this problem, investigating the potential of DRT service in Wayne County, U.S.A., whose dominant tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 29 publications
1
13
0
Order By: Relevance
“…For instance, the utility of DRT mode ( U DRT ) is calculated based on agents’ income level ( k ) and private car ownership ( l ) using Equation 1, where x denotes choice variables, and ρ and μ are alternative specific constants and marginal utility parameters, respectively. For a detailed description of DMC parameters used in this study, interested readers are referred to Kagho et al ( 18, 32 ).…”
Section: Methodsmentioning
confidence: 99%
“…For instance, the utility of DRT mode ( U DRT ) is calculated based on agents’ income level ( k ) and private car ownership ( l ) using Equation 1, where x denotes choice variables, and ρ and μ are alternative specific constants and marginal utility parameters, respectively. For a detailed description of DMC parameters used in this study, interested readers are referred to Kagho et al ( 18, 32 ).…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, some scholars argue that ride-pooling services might increase traffic congestion. For example, in their study of Demand Responsive Transit (DRT), Kagho et al [17] found that the introduction of such a service was likely to increase overall VKT slightly in Wayne County, Michigan. Another study conducted in the same area [18] confirmed this finding and concluded that the introduction of DRT can increase the VKT by 22%.…”
Section: Literature Reviewmentioning
confidence: 99%
“…To date, most studies on the impact of ride-pooling services have been conducted in cities/counties larger in population size than Birmingham metro area, which has a population of 0.89 million [29]. For instance, studies have been carried out in: Hangzhou, China [13] (8.24 million population [30]); Haikou City, China [14] (2.02 million population [30]); Berlin, Germany [15] (3.57 million population [30]); Santiago, Chile [16] (6.9 million population [30]); and Wayne County, Michigan [17,18] (1.77 million population [31]). Since the population size affects transportation demand, further research is needed to investigate how ride-pooling services affect the operational efficiency of the transportation system in medium-sized cities (population between 350,000-999,999).…”
Section: Literature Reviewmentioning
confidence: 99%
“…With the advancement of DRT, the field trial of it is a welcome subject of empirical research (e.g.- [24]), but not so where market approval is still being sought. In view of the ambitious task in a rural setting and abovestated caveats, the lack of a manageable a priori assessment of sustainability still proves to be a weak point.…”
Section: A Case-related Sustainable Development Assessmentmentioning
confidence: 99%
“…3, is considered prototypical in terms of its peripheral location, polycentricity, and medium-to-low population density. The renewed (24) exp…”
Section: Investigation Area and Initial Quantity Structurementioning
confidence: 99%